Yellowface - Kuang, R. F. (Rebecca F.) (New York, NY : William Morrow, an imprint of HarperCollinsPublishers, 2023)
"Authors June Hayward and Athena Liu were supposed to be twin rising stars. But Athenas a literary darling. June Hayward is literally nobody. Who wants stories about basic white girls, June thinks. So when June witnesses Athenas death in a freak accident, she acts on impulse: she steals Athenas just-finished masterpiece, an experimental novel about the unsung contributions of Chinese laborers during World War I. So what if June edits Athenas novel and sends it to her agent as her own work? So what if she lets her new publisher rebrand her as Juniper Song--complete with an ambiguously ethnic author photo? Doesnt this piece of history deserve to be told, whoever the teller? Thats what June claims, and the New York Times bestseller list seems to agree. But June cant get away from Athenas shadow, and emerging evidence threatens to bring Junes (stolen) success down around her. As June races to protect her secret, she discovers exactly how far she will go to keep what she thinks she deserves."--
Keywords: Authors -- Fiction; Authorship -- Fiction; Asian Americans -- Fiction; Impostors and imposture -- Fiction; Chinese American authors -- Fiction; Book industries and trade -- Fiction; Deception -- Fiction; Racism -- Fiction; Secrecy -- Fiction; Theft -- Fiction; Psychological fiction; Thrillers (Fiction)